MENINGKATKAN HASIL BELAJAR SISWA SMP KELAS IX MELALUI PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS PADA MATERI SISTEM REPRODUKSI MANUSIA - Lili Budiarti (Journal of Social Studies Arts and Humanities (JSSAH), 2022)
IMPROVING THE LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTS THROUGH THE APPLICATION OF THE TEAMS GAMES TOURNAMENTS LEARNING MODEL ON THE HUMAN REPRODUCTIVE SYSTEM MATERIALThis research departs from the phenomenon that occurs in the classroom that the low understanding and learning outcomes of students in learning Natural Sciences about the Human Reproductive System. Therefore, a teacher needs to consider learning strategies so that they can improve student learning outcomes. The research was carried out at Junior High School (SMP Negeri 8 Kota Bogor) and aimed (1) to determine the use of the Teams games tournaments learning model to improve student learning outcomes in science subjects regarding the Human Reproductive System (2) to describe the process of improving student learning outcomes in science subjects about systems Human Reproduction before and after using the Teams games tournaments model, (3) To measure the magnitude of the increase in student learning outcomes in science subjects about Human Reproductive Systems after using the Teams games tournaments model. The results of this study indicate that the application of the Teams games tournaments learning model can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before the implementation of the Teams games tournaments learning model, student learning outcomes only reached an average value of 70, then there was an increase after the implementation of the Teams games tournaments learning model to 77 in cycle 1 and 86 in cycle 2. From the description above, the researcher concluded that the application of the Teams games tournaments learning model adapted to learning materials can create a pleasant learning situation so that there is an increase in student learning outcomes. Therefore, researchers suggest that the application of the Teams games tournaments learning model be socialized and used as an alternative in science learning in schools within the Bogor City Education Office.